Effect of pulse width of a variable square pulse (VSP) erbium:YAG laser on the treatment outcome of periorbital wrinkles in Asians - Woraphong Manuskiatti (2018)
Background: Uses of appropriate laser parameters are essential for an optimum outcome with minimal risks of complications. Objective: To evaluate the effect of pulse width of a variable square pulse (VSP) Er:YAG laser on the treatment outcome. Methods: Twenty-four Thais with periorbital wrinkles received two treatments with a low-fluence, VSP Er:YAG laser resurfacing 1 month apart. Subjects were randomly divided into two groups and treated with two different parameters including a pulse width of 0.3 ms (short pulse, SP) for one group and a pulse width of 250 ms (super-long pulse, SL) for the other group. Assessments were evaluated at baseline, 1-month and 3-month follow-up visits. Results: After one treatment, 63.7% and 33.4% of the subjects in the SP and SL groups, respectively, were assessed to have obvious to marked improvement of their wrinkles. After two treatments, a higher percentage of the subjects were rated to have obvious to marked improvement including 91% and 66.7% in the SP and SL groups, respectively. There was no significant difference in therapeutic outcome between the SP and SL groups. Conclusions: There was no significant difference in efficacy and side effects, between the SP and SL groups. However, a trend toward better response with the shorter pulse width was observed. © 2010 The International Society of Dermatology.